Penilaian Gaya Belajar Model Honey-Alonso Mahasiswa Kimia FMIPA UNIMA - Freetje Waworuntu; Jeanne Maria Tuerah; Soenandar Milian Tompunu Tengker (Oxygenius: Journal Of Chemistry Education, 2022)
The Honey-Alonso model consists of 4 LS concepts namely Active Style (AS), Reflective Style (RS), Theoretical Style (TS), and Pragmatic Style (PS). The LS questionnaire consists of 80 statements, each LS has 20 statements. Test the validity of the instrument with SPSS 21 on the Scale – Reliability Analysis menu and the output is shown in the Item – Total Statistics – Corrected Item-Total Correlation table.The results of 58 respondents obtained AS = 9 (45%), TS = 18 (90%), RS = 13 (65%), and PS = 13 (65%) with a consistent reliability coefficient. The assessment is based on the total individual score for each LS and is converted to a z-score using the NORMDIST excel formula. In the range of normal distribution values are identified in 5 categories namely Very Good (VG), Good (G), Enough (E), Less (L), and Very Poor (VP). The results of the assessment are a combination of 17 typical learning styles. There are 41 respondents who have a strong learning style and 17 respondents who have a weak learning style. Learning styles need to be known by students as early as possible so they can improve it. A strong learning style can increase their learning achievement.